Biomineralization and Bioaccumulation of Europium by a Thermophilic Metal Resistant Bacterium - Maleke, Maleke; Valverde, Angel; Vermeulen, Jan-G; Cason, Errol; Gomez-Arias, Alba; Moloantoa, Karabelo; Coetsee-Hugo, Liza; Swart, Hendrik; van Heerden, Esta; Castillo, Julio (Frontiers in Microbiology, 2019)
Rare earth metals are widely used in the production of many modern technologies. However, there is concern that supply cannot meet the growing demand in the near future. The extraction from low-grade sources such as geothermal fluids could contribute to address the increasing demand for these compounds. Here we investigated the interaction and eventual bioaccumulation of europium (Eu) by a thermophilic bacterium, Thermus scotoductus SA-01. We demonstrated that this bacterial strain can survive in high levels (up to 1 mM) of Eu, which is hundred times higher than typical concentrations found in the environment. Furthermore, Eu seems to stimulate the growth of T. scotoductus SA-01 at low (0.01-0.1 mM) concentrations. We also found, using TEM-EDX analysis, that the bacterium can accumulate Eu both intracellularly and extracellularly. FT-IR results confirmed that carbonyl and carboxyl groups were involved in the biosorption of Eu. Infrared and HR-XPS analysis demonstrated that Eu can be biomineralized by T. scotoductus SA-01 as Eu2(CO3)3. This suggests that T. scotoductus SA-01 can potentially be used for the biorecovery of rare earth metals from geothermal fluids.